Assessing the value of surface water and groundwater quality improvements when time lags and outcome uncertainty exist: Results from a choice experiment survey across four different countries - Tobias Holmsgaard Larsen; Thomas Hedemark Lundhede; Søren Bøye Olsen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2020)
This report summarizes the main results from a choice experiment survey addressing peoples' willingness to pay (WTP) for improvements in surface water quality as well as groundwater quality. A particular novel focus is on estimating the extent to which WTP is impacted by the time lags and outcome uncertainties that commonly occur in practice when implementing new policies to improve water quality. The survey is conducted across four different case areas in four different countries, involving responses from more than 3000 respondents. Results generally confirm previous findings that people on average have quite high WTP for improvements in water quality, both in relation to surface water and groundwater. In addition, the results show that the WTPs reduce significantly with increasing time lags and outcome uncertainty in relation to the actual water quality improvements.
Keywords: C83; D60; Q51; Q53; 330; Economic Valuation; Choice Experiment; Water Quality; Outcome Uncertainty; Time Lags